La cartografía de los ingenieros militares. Instrumento para el conocimiento del territorio - Moncada Maya, José Omar (Revista de Geografía Norte Grande, 2018)
Among the numerous activities carried out by the Military Engineers in the American territories under Spanish sovereignty is the elaboration of maps, a task that was carried out by this Corps from the 16th to the 19th century. The objective of this article is to show how this was a consequence, on the one hand, of the academic training they received at the Mathematics Academies, and on the other hand, the professional practice developed at the service of the Crown. But above all, it is to show the impact that this activity had on the knowledge of the American territories, even though many of these maps were known many years later, since they accompanied detailed reports. This allowed them to be recognized as important collaborators in the tasks of organizing the American territories and access, in several cases, to important positions of government. The result of its work is cartography rich in themes, quality of representation and territorial diversity.